Highly pseudocapacitive Nb-doped TiO2 high power anodes for lithium-ion batteries. Issue 45 (16th October 2015) - Lübke, Mechthild; Shin, Juhun; Marchand, Peter; Brett, Dan; Shearing, Paul; Liu, Zhaolin; Darr, Jawwad A.
Abstract : Nb-doped and pure TiO2 (anatase) nanoparticles were synthesized via a continuous hydrothermal flow synthesis reactor and investigated as electrode material for lithium-ion batteries. Abstract : Nb-doped TiO2 (anatase) nanoparticles were synthesized using a continuous hydrothermal flow synthesis reactor using a supercritical water flow as a reagent and crystallizing medium. The as-prepared nano-powders with ca. 25 at% Nb 5+ (<6 nm diameter) were used as possible anodes for lithium-ion batteries without any further heat-treatment. Cyclic voltammetry and galvanostatic charge/discharge cycling tests were performed in the range of 1.2 to 3.0 V vs. Li/Li + . The Nb-doped TiO2 samples showed superior capacity retention at high current rates compared to the corresponding undoped nano-TiO2 . The superior performance of the doped samples (at specific currents up to 15 A g −1 ) was attributed to higher electronic conductivity and a greater charge storage contribution from surface effects like pseudocapacitance (Faradaic processes) as well as Helmholtz double layer charge storage.